A Heterozygous STXBP1 Gene de novo Mutation in an Iranian Child With Epileptic Encephalopathy: Case Report - Masoud Heidari; Morteza Soleyman-Nejad; Mohammad Hossein Taskhiri; Alireza Isazadeh; Manzar Bolhassan; Javad Shahpouri; Mansour Heidari; Nahid Sadighi (Acta Medica Iranica, 2020)
The Syntaxin Binding Protein 1 (STXBP1) plays an important role in regulating neurotransmitter release and synaptic vesicle fusion through binding to syntaxin-1A (STX1A) and changing its conformation. In this study, we identified a de novo mutation (c.C1162T: p.R388X) in exon 14 of the STXBP1 gene causing an epileptic encephalopathy, early infantile, non-epileptic movement, and unclassified infantile spasms disorders in a 5-year-old boy by whole-exome sequencing. The segregation of this genetic variant was examined in the patient as well as in his parents. We found the R388X in heterozygous state in the proband but not in his parents. This genetic change could be due to de nova mutation or germlinemosaicism.